Requirement model for POLIMAS examination evaluation system (PEES) - Ahmad, Amyzah; Yusop, Nor Iadah; Ta'a, Azman (2006)
Requirements play an important role in system development project.It is because requirement forms the backbone of any successful project and provides the measure of success or failure of a certain project.Misinterpretation of the requirements would increase cost and hinder the system development to meet users’ expectation.Therefore, it is necessary to present the requirement in an understandable and meaningful way.This is achievable through requirement model.The model will give a complete view of certain system and represent idea without having to develop an actual system.This research aims to create a requirement model for POLIMAS Examination Evaluation System (PEES). Unified Modeling Language (UML) notation is used to model out the requirements.Requirement model is validated by using horizontal prototype, the system requirements testing and test case.UML diagrams and a set of requirement list will be produced in this research.Several recommendations for future research will be discussed at the end of this paper.